2022
DOI: 10.1186/s12877-022-03345-4
|View full text |Cite
|
Sign up to set email alerts
|

The use of co-design in developing physical activity interventions for older adults: a scoping review

Abstract: Background Promoting physical activity (PA) participation in older adults is important for preserving quality of life and functional independence. Co-design has been shown to increase engagement of end-users in health-related policies and interventions. This scoping review aimed to examine how co-design has been used to develop PA interventions for older adults. Methods We searched MEDLINE, EMBASE, AMED, and CINAHL. Peer-reviewed primary research s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 82 publications
2
6
0
Order By: Relevance
“…The improvement in this group -7 of 10 could potentially be explained by the Hawthorne effect, that is, changes in outcomes due to being a participant in research 34 and the social benefit of these contacts. the intervention, better adherence, increased levels and improved PA. 35 There were no changes to the caregivers' physical function and activity with our study which has been found previously 36 possibly due to the short duration of the intervention. Similarly, there were no improvements in the care-recipients' outcomes, due to the chronicity of their nominated health conditions that impact on physical function and mobility.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…The improvement in this group -7 of 10 could potentially be explained by the Hawthorne effect, that is, changes in outcomes due to being a participant in research 34 and the social benefit of these contacts. the intervention, better adherence, increased levels and improved PA. 35 There were no changes to the caregivers' physical function and activity with our study which has been found previously 36 possibly due to the short duration of the intervention. Similarly, there were no improvements in the care-recipients' outcomes, due to the chronicity of their nominated health conditions that impact on physical function and mobility.…”
Section: Discussionsupporting
confidence: 44%
“…While Otago‐Plus is an individually tailored evidence‐based PA program and provides the benefits of a personalized program prescribed by a physiotherapist, 26 caregivers themselves were not consulted in the development of the intervention, or in planning their PA prescription according to their exercise preferences. Co‐designing PA interventions with older people may lead to the development of interventions that result in better satisfaction with the intervention, better adherence, increased levels and improved PA 35 . There were no changes to the caregivers' physical function and activity with our study which has been found previously 36 possibly due to the short duration of the intervention.…”
Section: Discussionsupporting
confidence: 44%
“…Overcoming barriers of physical inactivity with muti-pronged strategies such as easy access to motivational interviewing, personalized physical activity coaching and setting physical targets tailored to the individuals may promote adoption of a less sedentary lifestyle in older adults [ 92 ]. Such multi-component and complex strategies should be co-designed and structured to participant groups sociocultural context [ 93 ]. For sarcopenic participants with cognitive impairments, current studies exploring the biochemical process involved in muscle-brain cross talk are underway.…”
Section: Discussionmentioning
confidence: 99%
“…Co-design is a promising user-centred methodology that could be used for consultation. It incorporates the values, preferences and ideas of the end-users as they engage in continuous reflection and iteration to develop interventions and services while collaborating with researchers and other stakeholders [ 57 ]; this approach may enhance community health by meeting community public health needs [ 58 ].…”
Section: Discussionmentioning
confidence: 99%